Willingness-to-pay for ready-to-eat clean label food products at convenient stores - Jane Lu Hsu; Chin-Chang Sung; Jo-Ting Tseng (Future Foods, 2023)
Clean label food products using natural and fresh ingredients with minimal additives have gained popularity in the market. In this study, four types of ready-to-eat clean label food products [red bean bread (bread category), rosemary chicken lunch (lunch box category), lemon tea (beverage category), and sliced mango preserves (snack category)] available at convenient stores in Taiwan are selected for willingness-to-pay (WTP) measurement. A consumer survey was administered, and multivariate analyses (factor analysis, cluster analysis, MANOVA) are applied in data analytics. Results indicate that the increases in retail price for those in the high-WTP cluster ranged from 13.22% (Sliced mango preserves) to 14.06% (Lemon tea). For the low-WTP cluster, the increases in retail price ranged from 3.74% (Sliced mango preserves) to 4.35% (Bread). Findings in this study indicate that product involvement can be considered as the core factor for those who are willing to pay higher percentage of retail prices of ready-to-eat clean label food products at convenient stores. Ingredients and product labeling are important for potential customers to distinguish clean label food products from conventional products in the market.